Performance of Constructed Wetlands Cultivated with Tifton 85 (Cynodon Dactylon Pers.) - Collares, Maria Fernanda Antunes (2021)
The objective of the present study was to evaluate a vertical flow system (SACs), using crusher and sand, cultivated with Cynodon dactylon Pers., For the treatment of swine wastewater. The experiment was conducted from August to November 2017, in the experimental area of the Institute of Agricultural Sciences of UFMG. The experimental design was completely randomized with three replicates in each treatment. Data were submitted to ANOVA test and the means comparison test with 5% significance. It was observed that for the removal of COD, the treatments were statistically different, being able to highlight the high efficiency of treatment with gravel + plant reaching 96%. In the turbidity removal efficiency, total, fixed and volatile solids between treatments there was no significant difference, but it is possible to observe a considerable reduction of the evaluated parameters. For pH the highest average was with the treatment brita + plant and, for the electrical conductivity the highest average was the sand treatment. The cultivated tifton 85 showed good adaptation to the medium thus having a good growth and yield. Therefore, it was concluded that the system of floodwaters built for the treatment of swine wastewater is efficient, being recommended the use of cultivars such as tifton 85 because it is nutritious for animal feed.